3,5-Bis(4-bromophenyl)-1-phenyl-4,5-dihydro-1H-pyrazole - Samshuddin, S.; Narayana, B.; Yathirajan, H.S.; Safwan, A.P.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(21)H(16)Br(2)N(2), the central pyrazole ring adopts an flattened envelope conformation, with the stereogenic C atom in the flap position. The deviations from planarity for this ring are relatively minor (r.m.s. deviation = 0.045 angstrom) and the dihedral angles formed with the N- and C(imine)-bound benzene rings are 7.73 (13) and 11.00 (13)degrees, respectively. By contrast, the benzene ring bound at the chiral C atom is almost orthogonal to the rest of the molecule; the dihedral angle formed between this ring and the pyrazole ring is 79.53 (13)degrees. In the crystal, the packing is stabilized by C-H center dot center dot center dot N and C-H center dot center dot center dot Br interactions.